TRANSFORMASI DIGITAL UMKM PEREMPUAN PESISIR MELALUI MODEL BISNIS INKLUSIF BERBASIS TEKNOLOGI/SAINS/SENI - Ruray, Titiek Arafiani; Majojo, Muhammad Yasin; Yunus, Imran; Sudin, Idris (Universitas Kadiri, 2025)
The Women’s Joint Business Group in Guraping, Tidore Islands, faces low production capacity (5–10 kg/week), weak management without records or legality, and limited marketing confined to local networks without digital technology. This study implements an inclusive business model based on science, technology, and arts to enhance business capacity, strengthen governance, and expand market access for coastal women. Using a participatory method, the program proceeded through five stages: socialization, training in business management and digital marketing, application of appropriate technology (fish smoking and sago grating machines), implementation of Standard Operating Procedures, and continuous mentoring with pre- and post-tests. Results show notable progress: evaluation scores rose by 85.8 percent, production increased up to 300 percent, 75 percent of participants actively adopted digital marketing, and average income grew by 80 percent. The program transformed traditional business practices into modern, sustainable patterns through strengthened management, technology adoption, and wider market access.